The church and its mission in the New Testament and Early Christianity: essays in memory of Hans Kvalbein - Kvalbein, Hans; Aune, David Edward; Hvalvik, Reidar (Wissenschaftliche Untersuchungen zum Neuen Testament, 2018)
Cover -- Table of Contents -- Abbreviations -- David E. Aune: Introduction -- Reidar Hvalvik: Theology for the Church, Its Mission and the Christian Life: The Scholarly Profile of Professor Hans Kvalbein (1942-2013) -- Jostein Ådna: The Mission to Israel and the Nations: The Understanding of Mission in the Gospel of Matthew Reconsidered -- Ernst Baasland: Mission and Love of Enemy: Matthew 5:43-44 and Luke 6:27-28, 35 (2 Clem. 13.3 -- Diogn. 5) in Its Graeco-Roman Context -- Johannes Beutler SJ: Peter on theWay to His Universal Mission in the Gospel of John -- Reinhard Feldmeier: Ecclesia peregrinans: Luke's Concept of a Missionary Church -- Volker Gäckle: The Proclamation of the Kingdom of God in Acts -- Klaus B. Haacker: Frustrated Plans and Unexpected Outcome: Acts 16:6-8 Re-considered -- Rainer Riesner: The Gentile Mission of the Hellenists (Acts 11:19-21) and the Jesus Tradition -- Christoph Stenschke: Migration and Mission in the Book of Acts -- Peder Borgen: Perspectives for Mission: Galatians 3:1-14 in Context -- Halvor Moxnes: Who are the Children of Abraham in Romans 4? Retelling the Memory of Abraham "Our Ancestor" -- David E. Aune: John's Prophetic Commission and the People of theWorld (Rev 10:8-11) -- Torrey Seland: "Like Newborn Infants": The Readers of 1 Peter as Newly Converted Christians? -- Reidar Hvalvik: Mass Conversions, Persecutions and Church Growth: Critical Reflections on the Rapid Expansion of the Church During the First Three Centuries -- Karl Olav Sandnes: Households and the Exodus: A Note on Infant Baptism in the Early Church -- Oskar Skarsaune: Mapping 'p??ta t? ????': The Geographical Horizon of Early Christian Mission -- Reidar Hvalvik: Bibliography of Hans Kvalbein's Scholarly Publications -- List of Contributors -- Index of Ancient Sources -- Index of Modern Authors -- Index of Subjects